2022
DOI: 10.3390/nu14091978
|View full text |Cite
|
Sign up to set email alerts
|

Recent Information on Vitamin D Deficiency in an Adult Korean Population Visiting Local Clinics and Hospitals

Abstract: We retrospectively reviewed serum 25-hydroxy vitamin D (25(OH)D) test results from an adult Korean population visiting local clinics and hospitals between July 2017 and December 2021 to gather recent information on the prevalence of vitamin D deficiency. The prevalence of vitamin D deficiency status was investigated according to criteria offered by various clinical guidelines. During the study period, 180,289 subjects (29,658 men and 150,631 women) were tested for 25(OH)D. The overall prevalence rates of vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Our study showed that only 3% of subjects had vitamin D below 10 ng/mL, 10% had below 15 ng/mL, 22% had below 20 ng/mL, and 42% had below 30 ng/mL. This is in comparison to a very recent large study (180,289 subjects), in which the overall prevalence of vitamin D deficiency status based on 25(OH)D level was as follows: 0.4% for <5 ng/mL, 12.5% for <10 ng/mL, 20.6% for <12 ng/mL, 49.4% for <20 ng/mL, and <75.3% for <30 ng/mL [ 21 ]. Furthermore, Figure 1 , Figure 2 and Figure 3 show the data in graphical presentations that suggest that the levels of vitamin D, PTH, and ALK are skewed to the left.…”
Section: Resultscontrasting
confidence: 48%
“…Our study showed that only 3% of subjects had vitamin D below 10 ng/mL, 10% had below 15 ng/mL, 22% had below 20 ng/mL, and 42% had below 30 ng/mL. This is in comparison to a very recent large study (180,289 subjects), in which the overall prevalence of vitamin D deficiency status based on 25(OH)D level was as follows: 0.4% for <5 ng/mL, 12.5% for <10 ng/mL, 20.6% for <12 ng/mL, 49.4% for <20 ng/mL, and <75.3% for <30 ng/mL [ 21 ]. Furthermore, Figure 1 , Figure 2 and Figure 3 show the data in graphical presentations that suggest that the levels of vitamin D, PTH, and ALK are skewed to the left.…”
Section: Resultscontrasting
confidence: 48%
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the largest group of patients managed for IDA using ICD-10 D50 was comparable to the number of subjects in this study at Green Cross Laboratories. Considering that Green Cross Laboratories is a referral laboratory for local clinics and hospitals without their own clinical laboratories, and that older patients and those with comorbidities visit university hospitals and medical centers more frequently than others, the differences in patient population characteristics observed in this study may be due to the healthcare-related behaviors of patients [ 21 ]. In addition, the number of patients from the HIRA database includes repeated data from some subjects, which may lead to overestimates of utilization in specific age groups.…”
Section: Discussionmentioning
confidence: 99%